Epidemiology of fetal deaths: Specialized Maternal Perinatal Institute. 2003 - Huertas, Erasmo (2015)
OBJETIVES: To determine the frequency of stillbirth (IUFD) IV in a hospital level of care. MATERIALS AND METHODS: We reviewed the clinical records of all cases of stillbirths recorded in the database of the Directorate of Statistics and Informatics Specialized Maternal Perinatal Institute (IME), occurred between January 1 and December 31, 2003 . Relevant data were processed using the Perinatal Information System V 1.5. RESULTS: During the study period there were a total of 17,869 births, of which 130 were for intrauterine fetal deaths, giving a rate of 7.33 per thousand RNV. Maternal pathologies associated were: anemia in 40% of cases, preterm labor (33.1%) and preeclampsia / eclampsia (15.5%). The fetal pathology associated consisted of premature rupture of membranes, intrauterine growth restriction and congenital malformations. 9.2% of intrapartum IUFD presented. CONCLUSIONS: The rate of stillbirths in the IME remains within international averages. Prospective studies should be conducted to determine relative risks in different age groups as well as to evaluate management protocols of the major pathologies associated with the problem and the quality of prenatal care.